2008
DOI: 10.1029/2007gc001867
|View full text |Cite
|
Sign up to set email alerts
|

Evolving east Asian river systems reconstructed by trace element and Pb and Nd isotope variations in modern and ancient Red River‐Song Hong sediments

Abstract: [1] Rivers in east Asia have been recognized as having unusual geometries, suggestive of drainage reorganization linked to Tibetan Plateau surface uplift. In this study we applied a series of major and trace element proxies, together with bulk Nd and single K-feldspar grain Pb isotope ion probe isotope analyses, to understand the sediment budget of the modern Red River. We also investigate how this may have evolved during the Cenozoic. We show that while most of the modern sediment is generated by physical ero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
149
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(177 citation statements)
references
References 91 publications
14
149
1
Order By: Relevance
“…However, within the Indus system there are no major compositional differences between the sediments from the different tributaries, showing that these elements cannot be used as effective provenance proxies. Our work is consistent with studies of our Asian river systems that suggested that grain size and sorting characteristics of the sediment were the primary controls on REE compositions (Clift et al, 2008b).…”
Section: Apparent Agessupporting
confidence: 91%
“…However, within the Indus system there are no major compositional differences between the sediments from the different tributaries, showing that these elements cannot be used as effective provenance proxies. Our work is consistent with studies of our Asian river systems that suggested that grain size and sorting characteristics of the sediment were the primary controls on REE compositions (Clift et al, 2008b).…”
Section: Apparent Agessupporting
confidence: 91%
“…The Nd evolution in the Hanoi Basin showed that the middle Yangtze (downstream the First Bend) was once important source to the paleo-Red River and was lost from the paleo-Red River between 37 and 24 Ma (Clift et al, 2006). Nd, Pb data and U-Pb dating and Hf isotope analysis of zircons support the paleo-drainage pattern that the Songpan-Garze terrain once belonged to the paleo-Red drainage basin and was gone before 12 Ma or maybe much earlier (Clift et al, 2006(Clift et al, , 2008bvan Hoang et al, 2009). However no compelling evidence for the connection between the upper Yangtze (upstream the First Bend) and the paleo-Red River were found, but their data do not preclude this possibility (van Hoang et al, 2009).…”
Section: Introductionmentioning
confidence: 69%
“…Although study of the evolvement of the Yangtze River has a long history of more than 100 years, it is still controversial. Previous studies proposed that the Yangtze River can be dated back to the Cretaceous or the early Tertiary (Clark et al, 2004;Clift et al, 2006Clift et al, , 2008bJia et al, 2010;van Hoang et al, 2009), the early Quaternary (Fan et al, 2005;Kang et al, 2009;Yang et al, 2006;Zhang et al, 2008) or the late Pleistocene (Brookfield, 1998). Clark et al (2004) proposed that the Yangtze River was once the tributary of the so called ''paleo-Red River'' draining into the South China Sea and reorganized by sequential river capture and reversal events.…”
Section: Introductionmentioning
confidence: 98%
“…Each has experienced a similar early Holocene evolution as sea level rose following the Last Glacial Maximum, with delta initiation around 9000-8000 years ago (e.g., Changjiang Delta, Hori et al (2002); Red River Delta, Tanabe et al (2006); Mekong River Delta, Ta et al (2005); Indus River Delta, Clift et al (2008)). Sedimentary facies successions of the individual deltas imply a complex scenario following an abrupt acceleration of sealevel rise around 9000-8500 years ago (Hori and Saito, 2007b).…”
Section: Asian Mega Deltasmentioning
confidence: 99%